2011
DOI: 10.1177/0883073811408090
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cerebral Sinovenous Thrombosis

Abstract: Neonates are known to have a higher risk of cerebral sinovenous thrombosis than children of other age groups. The exact incidence in neonates remains unknown and is likely to be underestimated, as clinical presentation is nonspecific and diagnosis can only be made when dedicated neuroimaging techniques, including computed tomographic venography or magnetic resonance venography, are performed. Associated intracranial lesions are common and some, such as a unilateral thalamic hemorrhage, should suggest cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In CSVT, preterm neonates often present with more extensive white matter damage, whereas full-term neonates usually present with punctate white matter lesions [34]. The rapid development of the nervous system during the preterm period makes the brain highly vulnerable to hypoxic insults; the combination of destructive insults and developmental changes may result in extensive white matter injury [35][36][37]. However, even if white matter injury is usually more extensive in preterm babies, prematurity does not appear to be itself a risk factor for CSVT [37].…”
Section: Discussionmentioning
confidence: 99%
“…In CSVT, preterm neonates often present with more extensive white matter damage, whereas full-term neonates usually present with punctate white matter lesions [34]. The rapid development of the nervous system during the preterm period makes the brain highly vulnerable to hypoxic insults; the combination of destructive insults and developmental changes may result in extensive white matter injury [35][36][37]. However, even if white matter injury is usually more extensive in preterm babies, prematurity does not appear to be itself a risk factor for CSVT [37].…”
Section: Discussionmentioning
confidence: 99%
“…CSVT rarely affects children, with a reported childhood incidence of 0.67/100,000 in a large multicenter Canadian study 4) . In a study by the International Pediatric Stroke Study Group, more than half of the episodes of childhood CSVT occurred in newborns aged less than 28 days 4 5) , and it was concluded that neonates were at a higher risk for developing CSVT than older children 6) . In recent years, neonatal CSVT has become a more recognized clinical condition, mainly due to better awareness and improved neuroimaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Ventriculomegaly (hydrocephalus) Vascular abnormalities Suspected hypoxic ischemic injury (hypoxic ischemic encephalopathy) …”
Section: Indicationsmentioning
confidence: 99%
“…[1][2][3][4][5] • Vascular abnormalities. [2][3][4][5][8][9][10] • Suspected hypoxic ischemic injury (hypoxic ischemic encephalopathy). [2][3][4][5][11][12][13][14][15] • Patients on hypothermia, extracorporeal membrane oxygenation, and other support machines.…”
Section: Indicationsmentioning
confidence: 99%